Paul : The Apostle's Life, Letters, and Thought - Sanders, E. P. (Book collections on Project MUSE., 2015)
Decades after setting the study of Paul on a profoundly new footing with Paul and Palestinian Judaism (Fortress Press, 1977), E. P. Sanders now offers an expansive introduction to the apostle, navigating some of the thorniest issues in scholarship in language accessible to the novice and seasoned scholar alike. Always careful to distinguish what we can know historically from what we may only conjecture, and these from dogmatically driven misrepresentations, Sanders sketches a fresh picture of the apostle as an ardent defender of his own convictions, ever ready to craft the sorts of arguments that now fill his letters but--as Sanders carefully argues--were not the basis for his own beliefs and attitudes. He also gives sustained attention to a historical sketch of Paul's context, particularly Second Temple Judaism, in order to set comparisons of Paul and that context on solid ground. Here are familiar themes from Sanders's earlier work--the importance of works in Paul's thought, the relationship of "plight" and "solution"--in a presentation that reveals a career's reflection, along with new thinking regarding development in Paul's thought. All of the letters are carefully introduced in a text that will prove a worthy guide to the student and interested reader.